Constructing the Minimum Coverage of the I Graph (Texas Journal of Engineering and Technology, 2022)
Describes the structural methods of testing programs such as branch testing, program verification, symbolic testing and the generation of structural tests. An algorithm for the minimum coverage of the program graph based on a packaged adjacency matrix and a specific example of the minimum coverage of the program graph are introduced